1966
DOI: 10.1126/science.154.3753.1192
|View full text |Cite
|
Sign up to set email alerts
|

Noncollagenous Nature of the Proteins of Shark Enamel

Abstract: The proteins, soluble and insoluble at neutral pH, of relatively mature enamel of two different species of sharks were distinctly different from both collagen and embryonic enamel proteins and similar to the proteins isolated from mature human and bovine enamel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Noncollagenous proteins are believed to be present in the enameloid matrix (Everett and Miller, 1981;Goto, 1978b;Kobayashi, 1993;Levine et al, 1966). However, the details are still unknown.…”
Section: Tubular Vesicles Are the Major Component In The Enameloid Mamentioning
confidence: 97%
“…Noncollagenous proteins are believed to be present in the enameloid matrix (Everett and Miller, 1981;Goto, 1978b;Kobayashi, 1993;Levine et al, 1966). However, the details are still unknown.…”
Section: Tubular Vesicles Are the Major Component In The Enameloid Mamentioning
confidence: 97%
“…Their methods of biochemical analysis differed in some im portant respects to ours ), and while they disagree with our designation of this organic m atrix as a collagen, they wholeheartedly agree with the only biologically im por ta n t point we m ade; i.e., th a t this shark enamel m atrix is ectoderm al in origin (Levine et al [1966]). …”
Section: The Co-participation Hypothesis A)mentioning
confidence: 97%
“…The data presented corroborate evidence for enamel biogenesis provided by a number of studies in disparate vertebrate species that have suggested the anionic enamel proteins are expressed before amelogenins. Levine et al [33] showed that protein(s) of shark enameloid have an amino acid composition similar to that of enamelins, but do not contain amelogenins. Enamelins appear to be expressed prior to amelogenins in fetal bovine teeth [72].…”
Section: Classification Of Enamel Polypeptides According To Temporal mentioning
confidence: 99%